A techno-economic analysis of geothermal ejector cooling system. (15th February 2020) - Habibi, Mohammad; Aligolzadeh, Farid; Hakkaki-Fard, Ali
Abstract: Ground-coupled ejector cooling (GCEC) systems have been introduced to solve the air-coupled ejector cooling (ACEC) systems problems. To date, no research study is dedicated to compare the GCEC and the ACEC systems and determine the relative payback period of the GCEC system vs. the ACEC system. Furthermore, almost all the previous studies simulated the GCEC systems by elementary models. Therefore, a comprehensive simulation is conducted to assess the techno-economic performance of a GCEC system. The model consists of the ejector and the borehole heat exchanger submodels. The first section of the results compares the ACEC system and the GCEC system during a cooling season. The seasonal coefficient of performance of the GCEC system is 83% higher than that of the ACEC system. The maximum building load per borehole heat exchanger unit length is 12.4, 17.5, and 21.6 W/m when the soil thermal conductivity is 1.40, 2.45, 3.50 W/(m.K), respectively. The second section of the results compares the relative payback period of the GCEC systems vs. the ACEC system for different values of soil thermal conductivities, borehole cost, and natural gas price. The relative payback period of the GCEC system vs. the ACEC system can be as low as five years. Highlights: The performance of the ACEC and GCEC systems are evaluated during a cooling season. A proper ejector (ejector B) is designed for the GCEC system. The seasonal COP of the GCEC system is 83% higher than that of the ACEC system. The RPP of the GCEC vs. the ACEC system is analyzed for different parameters. The RPP of the GCEC vs. the ACEC system can be as low as five years.